Journal of The Effect of Self-Efficacy, Work Motivation and Job Satisfaction on The Work Performance of Indonesian Migrant Workers Working Cycle Job (28/28) in Qatarxxx - Xxx - Ahmad Budairy Yusi; Tubagus Ismail; Pardamean Daulay (Dinasti Publisher, 2024)
Every successful organization will always be supported by a base of employees who are committed to its work. High self-efficacy, high motivation and high job satisfaction are manifestations of the commitment of high-performing employees. Company performance is a representation of how strong an organization is able to survive in the business world, while employee performance is a representation of how much the company is able to achieve the vision and mission of its organization. The workforce working in Qatarxxx - XXX, 93.5%, is a professional workforce who is an expatriate, while local employees are mostly top managements who fill critical positions in the company, while expatriates come from various countries in the world, namely from countries in Europe, Africa and Asia, including Indonesian migrant workers totaling 31 people. With a cycle job work system (28/28), which is 28 days of work without a holiday in the middle of the sea, and 28 days OFF in each country this will potentially make a work situation that is stressful, bored and loses morale because you have to work for 28 days without a holiday in the middle of the sea. Quantitative research conducted on 30 Indonesian migrant workers, showed that migrant workers from Indonesia can survive the cycle job work environment (28/28) because of the influence of self-efficacy (86.38%), followed by the influence of job satisfaction (85.64%), and then the influence of motivation (84.16%).